Islamic Family Law Juridical Analysis of Case Number 014/Pdt.P/2015/PA.Stg Regarding Refusal of Kawing Dispensation at the Sintang Religious Court - Wiranti, Wiranti; Muhibbin, Mohamad; Thamrin, Dahlan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The problems that occurred in the field, especially in the Sintang Class II Religious Court, were found from all the existing cases, there was one case that was rejected, namely case Number 014/Pdt.P/2015/PA.Stg. The purpose of this study is to describe and analyze the basic considerations of the judges of the Sintang Religious Court, the Juridical Factors against the rejection of the marriage dispensation, and the legal consequences of the rejection of the marriage dispensation based on the case decision Number 014/Pdt.P/2015/PA.Stg. This study uses a descriptive method with a qualitative approach. Data collection techniques are carried out through interviews, observation and documentation, and data analysis techniques are carried out by data reduction, data display and drawing conclusions. The results of this study indicate that the marriage dispensation procedure at the Sintang religious court is in accordance with the rules, only in case number 014/Pdt.P/2015/ PA.Stg.hakim using the rule. heavier harm by doing the lighter of the two.